Mood Stabilizer Medication Adherence in Bipolar Patients During Covid-19 with MMAS-8 Method - Kusumahati, Eva; Herliani, Leni; Rustiningsih, Rustiningsih (Indonesian Journal of Multidisciplinary Science, 2023)
Bipolar is a relapsing disease, a longer duration of treatment is expected to achieve the success of initial therapy. Mood stabilizers are medications to control the mood of people with bipolar disorder. The purpose of the study is to determine adherence to taking mood stabilizer drugs in bipolar patients during the Covid-19 pandemic. The research used descriptive quantitative method with non-probability sampling and the MMAS-8 questionnaire as the instrument. The researchers analyzed data starting from the editing, coding, to processing stages with the help of software. The results of the study show that 21.3% of the drugs used were risperidone. Respondents forgot to take medication as much as 85.3%. Respondents for two weeks did not take medication as much as 78.7%. As many as 60% of respondents had reduced the use of drugs. As many as 72% of respondents have forgotten to bring their medicine when traveling. As many as 81.3% of respondents had taken medicine yesterday. As many as 64% of respondents stopped taking the drug. As many as 77.3% of respondents feel uncomfortable taking medicine every day. As many as 82.7% of respondents had difficulty taking medicine. In conclusion, 87.5% did not comply with taking mood stabilizing drugs during the Covid-19 pandemic and 12.5% ??complied, because during the Covid-19 pandemic, access to control was limited so that it was difficult to get medicine.